The Role of School Culture and Climate in Creating A Conducive and Enjoyble Learning Environment - Baihaqi, Muhammad Affan; Sutama, S (Proceedings International Conference on Education Innovation and Social Science, 2025)
School culture and climate are two fundamental pillars that interact in shaping the quality of the learning environment. Although these aspects have received attention in various educational policies, the implementation of school cultural values and the development of a healthy school climate still face several challenges, such as bureaucratic dominance, resistance to change, and the limited socio-emotional competencies of educators. This study aims to explore in depth the role of school culture and climate in creating a conducive and enjoyable learning environment for students in Indonesia. This research employs a descriptive qualitative approach using a literature review method. Data were collected through a systematic review of relevant national sources, including scholarly books, accredited journal articles, and official policy documents published in the last ten years. The data were analyzed thematically and critically to examine the relationship between school culture, school climate, and the quality of the learning environment. The findings indicate that a school culture that upholds values of collaboration, openness, and appreciation for diversity contributes to a school climate that supports students’ psychological well-being and active engagement in learning. Conversely, a school culture that is closed, authoritarian, and bureaucratic tends to create a rigid and pressuring learning climate. Therefore, synergy between school culture and climate is a strategic key to establishing an effective, enjoyable, and meaningful learning process.